Evidence for topographic organization in the cerebellum of motor control versus cognitive and affective processing - Stoodley, Catherine J. (2010)
Patients with cerebellar damage often present with the cerebellar motor syndrome of dysmetria, dysarthria and ataxia, yet cerebellar lesions can also result in the cerebellar cognitive affective syndrome, including executive, visual-spatial, and linguistic impairments, and affective dysregulation. We have hypothesized that there is topographic organization in the human cerebellum such that the anterior lobe and lobule VIII contain the representation of the sensorimotor cerebellum; lobules VI and VII of the posterior lobe comprise the cognitive cerebellum; and the posterior vermis is the anatomical substrate of the limbic cerebellum. Here we analyze anatomical, functional neuroimaging, and clinical data to test this hypothesis. We find converging lines of evidence supporting regional organization of motor, cognitive, and limbic behaviors in the cerebellum. The cerebellar motor syndrome results when lesions involve the anterior lobe and parts of lobule VI, interrupting cerebellar communication with cerebral and spinal motor systems. Cognitive impairments occur when posterior lobe lesions affect lobules VI and VII (including Crus I, Crus II, and lobule VIIB), disrupting cerebellar modulation of cognitive loops with cerebral association cortices. Neuropsychiatric disorders manifest when vermis lesions deprive cerebrocerebellar limbic loops of cerebellar input. We consider this functional topography to be a consequence of the differential arrangement of connections of the cerebellum with the spinal cord, brainstem, and cerebral hemispheres, reflecting cerebellar incorporation into the distributed neural circuits subserving movement, cognition, and emotion. These observations provide testable hypotheses for future investigations.